2012
DOI: 10.5761/atcs.cr.11.01756
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting Aneurysm in A Patient with Autosomal Dominant Polycystic Kidney Disease

Abstract: Autosomal dominant polycystic kidney disease (ADPKD) is primarily associated with renal failure, but it also causes systemic diseases, including cysts of other systemic organs and cerebral or visceral aneurysm. To make matters worse, life-threatening aortic diseases are associated with ADPKD in some cases. However, only a few reports of ADPKD-associated with thoracic aortic dissection have been published. Herein, we present a case of dissecting aneurysm in a patient with hypertension and ADPKD. He had been fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…The study selection process is represented in Figure 3. We report data from 27 cases ( Table 1) of ADPKD patients with AD, of which 25 were previously identified from the literature [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] and two from our clinical experience. A schematic representation of age, hypertension and CKD stage distribution in the study population is reported in the Figure 4.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study selection process is represented in Figure 3. We report data from 27 cases ( Table 1) of ADPKD patients with AD, of which 25 were previously identified from the literature [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] and two from our clinical experience. A schematic representation of age, hypertension and CKD stage distribution in the study population is reported in the Figure 4.…”
Section: Resultsmentioning
confidence: 99%
“…However, additional manifestations are often described, including: intracranial, coronary and other arterial aneurysms, arterial dolichoectasias, aortic or cervicocephalic arteries dissections, and heart valve diseases . Although ADPKD‐AD association has been previously reported, only few cases are available in the literature and a systematic review has never been made. We report two cases of AD in ADPKD patients from our experience and perform a systematic analysis of the literature.…”
mentioning
confidence: 99%
“…These consist of a variety of conditions targeting the aorta, with the most common forms being aneurysm [1,2], dissection [3,4], occlusion owing to atherosclerosis [5,6] and a general stiffening of the normally elastic aorta that is thought to be a natural consequence of ageing ( [7][8][9][10][11]; table 1). There are many co-morbid abnormalities that can lead to or be associated with one or more of these conditions, including hypertension [12][13][14], genetic mutations (such as Marfan syndrome (MFS) [15,16]), developmental defects (such as bicuspid aortic valve (BAV) [17 -19]), connective tissue disorders (such as Ehler -Danlos disorder [20,21], scleroderma [22,23], osteogenesis imperfecta [24,25], polycystic kidney disease [26,27] and Turner syndrome [28,29]), as well as injury. The co-morbid abnormalities that will be discussed below are shown in table 1.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] There are also reports in the literature of patients with aneurysms and dissections of other large arteries, including the aorta. [11][12][13][14][15] The connection between ADPKD and these vascular phenotypes has led to the hypothesis that polycystin signaling plays a role in maintaining vascular integrity. 16,17 Several lines of experimental data are consistent with this concept.…”
mentioning
confidence: 99%